Interlocking and Automatic Operating System Design with Automaton Method - Dincel, Emre; Kurtulan, Salman (Elsevier BV, 2012)
Abstract Interlocking systems are one of the most important elements of railway signalization systems in order to ensure safe transportation. Software design of the interlocking systems can be performed by different methods such as automaton method, petri nets. These systems can be implemented by mechanical components or electronic devices such as Programmable Logic Controllers (PLCs). In this study, an interlocking system is designed by using automaton method for a sample railway simulator so that trains can move in a safe manner. In addition, in order to provide complete automatic operation, another system is also designed. Then both designed interlocking and automatic operation systems are implemented in Beckhoff CX1010 PLC and tested on simulator with the help of human interface that is created for this purpose.